20‐3: Invited Paper: BEOL‐Compatible Ferroelectric Field‐Effect Transistors with Atomic Layer Deposition of Oxide Semiconductor Channel Toward Monolithic 3D Integration. Issue 1 (28th June 2022) - Lin, Zhiyu; Lin, Zehao; Wang, Ziheng; Si, Mengwei; Ye, Peide D.
Abstract : In this work, we report a BEOL‐compatible ferroelectric field‐effect transistor using oxide semiconductor as channel and ferroelectric hafnium zirconium oxide as gate insulator all grown by atomic layer deposition with a low thermal budget of 400°C, and meanwhile demonstrating well‐behaved ferroelectric characteristics.